Formation and training of little doctors as an effort to improve health in the SDN 37 Pekanbaru City - Melly Melly; Magdalena Magdalena; Elvi Asnaty; Kurniawati Kurniawati (Universitas Muhammadiyah Magelang, 2023)
Little doctors are students who receive training to actively participate in health activities at school, especially within the School Health Unit (UKS). The aim of this program is to enhance UKS activities at SD Negeri 37, Pekanbaru City, and to encourage all school members to maintain and improve their personal health and the school environment. The program involves the formation of little doctors and the provision of training to students regarding the little doctor program. This program encompasses the preparation, implementation, and evaluation stages. The program's outcomes include the formation of 40 little doctors from classes 4 and 5. After completing the training, 25 little doctors (62.5%) displayed good knowledge, and 30 little doctors (75%) improved their skills. To sustain the program, motivation and support from schools and local health centers are essential.